3, 4-diaminopyridine for the treatment of Lambert–Eaton myasthenic syndrome. (November 2010) - Wirtz, Paul W; Titulaer, Maarten J; Gerven, Joop MA van; Verschuuren, Jan J
The Lambert–Eaton myasthenic syndrome (LEMS) is an autoimmune disease in which antibodies against voltage-gated calcium channels inhibit cholinergic neurotransmission. LEMS is clinically characterized by muscle weakness and autonomic dysfunction. 3, 4-diaminopyridine (3, 4-DAP) blocks potassium channels in nerve terminals, resulting in an increase in acetylcholine release. This article describes the four randomized placebo-controlled trials of 3, 4-DAP in patients with LEMS. All trials demonstrated a significant effect on muscle strength and compound muscle action potential amplitude. Furthermore, the safety and tolerability of 3, 4-DAP are reviewed. The side effects of 3, 4-DAP are generally mild and most frequently consist of paresthesias, but epileptic seizures and arrhythmias have been described in patients using high doses. Given the efficacy and safety of 3, 4-DAP in LEMS, this drug is the mainstay for symptomatic treatment of LEMS.